Variasi Diameter Nozzle Terhadap Lamanya Proses Vakum Pada Fresh Water Generator di Laboratorium Polimarin - Khaeroman Khaeroman; wahyu Ari Putranto; Susanto Susanto; Rifki Arya Wiguna; Agung Nugroho (Jurnal Maritim Polimarin, 2021)
Ejector is a static pump which is worked by a vacuum principal. A vacuum which is happened in the ejector affect the performance and the ability of suction on the secondary mass flow section. A vacuum ejector in the fresh water generator affects the amount of fresh water which is generated. The objective of this research is to know the affection of variation in the outlet diameter of the nozzle towards secondary mass flow, especially on the air suction section (vacuum). In this research, an analysis has been done in a fresh water generator (FWG) with three alternative design of the outlet diameter of the nozzle using Computer Fluid Dynamics (CFD) method to get the optimal performance. The inlet pressure of primary flow is regulated to be steady at 3 bars. The variations of the diameter outlet of the nozzle are 4, 6, and 8 mm. The distance between the edge of the nozzle with outlet flow of the pipe is made at a settled position. The edge of the nozzle is at 3 mm inside the outlet flow of the pipe measured from the inside edge of the pipe. The result of CFD method is shown that on the variation of the outlet diameter of the nozzle 8 mm has the biggest mass flow (4.6838048 kg/s) between 4 and 6 mm. The implication of this research is that the outlet diameter of the nozzle 8 mm has the maximum value of a vacuum.